Plasmodium knowlesi Malaria in Malaysia - Balbir, Singh; Daneshvar, C. (Malaysian Medical Association, 2010)
Plasmodium knowlesi, a simian malaria parasite, is now recognised as the fifth cause of human malaria and can lead to fatal infections in humans. Knowlesi malaria cases are widely distributed in East and West Malaysia and account for more than 50% of admissions for malaria in certain hospitals in the state of Sarawak. This paper will begin with a description of the early studies on P. knowlesi, followed by a review of the epidemiology, diagnosis, clinical and laboratory features, and treatment of knowlesi malaria.